2015
DOI: 10.1038/srep18325
|View full text |Cite
|
Sign up to set email alerts
|

The aglycone of ginsenoside Rg3 enables glucagon-like peptide-1 secretion in enteroendocrine cells and alleviates hyperglycemia in type 2 diabetic mice

Abstract: Ginsenosides can be classified on the basis of the skeleton of their aglycones. Here, we hypothesized that the sugar moieties attached to the dammarane backbone enable binding of the ginsenosides to the sweet taste receptor, eliciting glucagon-like peptide-1 (GLP-1) secretion in the enteroendocrine L cells. Using the human enteroendocrine NCI-H716 cells, we demonstrated that 15 ginsenosides stimulate GLP-1 secretion according to the position of their sugar moieties. Through a pharmacological approach and RNA i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(36 citation statements)
references
References 38 publications
3
33
0
Order By: Relevance
“…Culturing the cells on the matrigel-precoated culture dishes causes the cells to exhibit the properties of enteroendocrine L cell, including their chromogranin and proglucagon expressions 15 , 16 . NCI-H716 cells secrete GLP-1 in response to a number of neurotransmitters, nutrients and secretagogues, as described in numerous studies 7 9 , 16 In the endocrine-differentiated NCI-H716 cells, geraniol, a monoterpene alcohol abundant in geraniums, grapes, lemons, and roses, exhibited the most significant GLP-1 stimulatory effect (Fig. 1a ).…”
Section: Resultssupporting
confidence: 56%
See 2 more Smart Citations
“…Culturing the cells on the matrigel-precoated culture dishes causes the cells to exhibit the properties of enteroendocrine L cell, including their chromogranin and proglucagon expressions 15 , 16 . NCI-H716 cells secrete GLP-1 in response to a number of neurotransmitters, nutrients and secretagogues, as described in numerous studies 7 9 , 16 In the endocrine-differentiated NCI-H716 cells, geraniol, a monoterpene alcohol abundant in geraniums, grapes, lemons, and roses, exhibited the most significant GLP-1 stimulatory effect (Fig. 1a ).…”
Section: Resultssupporting
confidence: 56%
“…The negative control siRNA did not affect the OR1A1 , OR1G1 , GNAL , CNGA2 , and GNAT3 expression levels in differentiated NCI-H716 cells. Endocrine-differentiated NCI-H716 cells were transfected with the siRNA duplexes using Lipofectamine RNAiMAX reagent (Invitrogen, Carlsbad, CA, USA) as previously described 9 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Kim et al screened the GLP-1 release ability of 15 ginsenosides and found that Rg3 showed the strongest GLP-1 secretion (about 27 pM/mg) effect in NCI-H716 cells. In this in vivo trial, 10 µM Rg3 significantly raised production of GLP-1 and insulin to reduce blood glucose in db/db mice [33]. In mouse islet cells, insulin secretion was significant: 2.3 times higher in the 4 µM Rg3 treatment group compared to control group [34].…”
Section: Potential Mechanisms Of the Anti-diabetic Effect Of Ginsengmentioning
confidence: 77%
“…Together the above results, it appears that DMC elicited its anti-hyperglycemic effects by enhancing GSK-3β activity and upregulating β-catenin expression, which in turn transactivated TCF7L2 that subsequently stimulated the secretion of GLP-1 and GIP leading to hypoglycemia. To further test this notion, we employed pharmacological tools and looked at the changes of these components in enteroendocrine cell line NCI-H716 cell, which is commonly used for measuring GLP-1 secretion 30 31 . Rheum Emodin is the main component of DMC (see Fig.…”
Section: Resultsmentioning
confidence: 99%